PROPHETIC VALUES IN AIK LEARNING (AL-ISLAM AND KEMUHAMADIYAH AT MUHAMMADIYAH HIGH EDUCATION: Case Study at Muhammadiyah University of Purworejo - Hermawan Hermawan (Universitas Muhammadiyah Surakarta, 2022)
Al-Islam and Kemuhammadiyahan (AIK) must be part of the efforts of Muhammadiyah universities to achieve the vision and mission of Muhammadiyah universities, namely